2x(x+2x)=36

Simple and best practice solution for 2x(x+2x)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x+2x)=36 equation:



2x(x+2x)=36
We move all terms to the left:
2x(x+2x)-(36)=0
We add all the numbers together, and all the variables
2x(+3x)-36=0
We multiply parentheses
6x^2-36=0
a = 6; b = 0; c = -36;
Δ = b2-4ac
Δ = 02-4·6·(-36)
Δ = 864
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{864}=\sqrt{144*6}=\sqrt{144}*\sqrt{6}=12\sqrt{6}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-12\sqrt{6}}{2*6}=\frac{0-12\sqrt{6}}{12} =-\frac{12\sqrt{6}}{12} =-\sqrt{6} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+12\sqrt{6}}{2*6}=\frac{0+12\sqrt{6}}{12} =\frac{12\sqrt{6}}{12} =\sqrt{6} $

See similar equations:

| 3/4(20y−8)+5=12y+1/4(20y+8) | | v3=-6 | | 4x+11=20–2x | | 22+16x=182 | | 4.x-3=3x(7 | | -30=-2+7m | | 5.1x+7.4-1.8x=9.1 | | x^2+9x=6x+5 | | (x−4)^3/4=8 | | (7x+26)+(2x+10)=180 | | -4(3+4m)=-16 | | 44=-4(1-6a) | | 12+7.5n=8+7.9n | | (6x-5)+(90-x)=90 | | 2x²+12x+16=0/2 | | 60h=225−50h | | 4x+14=7+x+14 | | (6x-5)+(180-x)=90 | | (6x-5)+(6x-95)=90 | | 1-4v=17 | | 2(4c+7)=21+c | | (6x-5)+(95-6x)=90 | | 5k-5=k+6 | | (6x-5)+(85-6x)=90 | | 3(x-4=-2(4-x) | | –11u+8u+–2u+–15=–10 | | -44=4(1-3n) | | (7x+5)=47 | | 1-4v=-17 | | 0.2=z/528 | | 0.5+0.4=0.7x-0.4 | | 8=3/4a+13-a+4 |

Equations solver categories